Opportunities for improved detection of linked hydroclimate‐ecosystem dynamics in Arctic catchments - Mård, Johanna; Christensen, Torben Røjle; Culp, Joseph M.; Goedkoop, Willem; Marttila, Hannu; Schmidt, Niels Martin; Vihma, Timo (Frontiers in Environmental Science, 2026)
Climate warming is transforming Arctic landscapes through changes in the cryosphere and water systems that together contribute to alterations in the structure and function of ecosystems. To better understand these interlinked processes and feedbacks, previous research has recommended studies at the catchment scale that explicitly couple hydroclimatic fluxes and their interactions with the environment. However, using such an approach requires coordinated cross-disciplinary monitoring. In this review, we synthesize knowledge on available monitoring of key hydroclimate and ecosystem indicators to identify opportunities to use a catchment-based approach for improved understanding of climate-ecosystem dynamics in the Arctic. There is overall a small spatial overlap between the coverage of hydroclimate and ecosystem monitoring. In-situ monitoring of both climate and hydrological variables is sparse with a northward decline in observation density, while most ecosystem monitoring is focused around accessible regions and near Arctic research stations. As a result, our study shows that only two catchments within the pan-Arctic drainage basin include monitoring of both hydroclimate and ecosystem variables. Although this general spatial mismatch results in a limitation in using a catchment-based approach to study hydroclimate-ecosystem interactions across the Arctic, there are opportunities in some data rich regions. We have identified 32 catchments that include monitoring of all hydroclimate variables. These can be used as a starting point for catchment-based approaches to study climate-ecosystem interactions, and continued improvement of observation methods can further help identify regions with the best potential for downscaling climate model output for future projections. But this requires prioritized coordinated ecological and hydroclimatic monitoring efforts in regions most vulnerable to climate change.